2010
DOI: 10.1002/hep.23323
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Maintenance Beyond One Year After Hbeag Seroconversion Is A Major Factor for Sustained Virologic Response in Hbeag-Positive Chronic Hepatitis B

Abstract: The reported durability of virologic response after successful lamivudine monotherapy is variable, and the question remains as to whether virologic responses can be maintained over an extended follow-up period. The aim of this study was to investigate posttreatment durability, the optimal duration of additional treatment after HBeAg clearance or seroconversion, and determinants for sustained virologic response (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 26 publications
12
105
2
Order By: Relevance
“…However, when consolidation treatment [2,4,5,8] was performed before termination of lamivudine treatment or when patients were young [4][5][6][7][8], the rate of virologic relapse was dramatically reduced. In 178 patients with HBeAg-positive chronic HBV infection that showed HBV DNA loss as well as HBeAg loss with lamivudine treatment, virologic relapse rates of 15.9% and 30.2% 1 and 5 years after stopping treatment, respectively were seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when consolidation treatment [2,4,5,8] was performed before termination of lamivudine treatment or when patients were young [4][5][6][7][8], the rate of virologic relapse was dramatically reduced. In 178 patients with HBeAg-positive chronic HBV infection that showed HBV DNA loss as well as HBeAg loss with lamivudine treatment, virologic relapse rates of 15.9% and 30.2% 1 and 5 years after stopping treatment, respectively were seen.…”
Section: Discussionmentioning
confidence: 99%
“…In 178 patients with HBeAg-positive chronic HBV infection that showed HBV DNA loss as well as HBeAg loss with lamivudine treatment, virologic relapse rates of 15.9% and 30.2% 1 and 5 years after stopping treatment, respectively were seen. It has also been reported that when patients were younger than 40 or underwent 1 or more year(s) of consolidation treatment the durability of sustained viral suppression was increased [8]. Patients who used clevudine or entecavir (n=48) to maintain HBV DNA levels at less than 300 copies/mL and HBeAg seroconversion for 6 months or more, experienced an accumulated virologic relapse of 41% and 60% after 12 and 24 months off therapy respectively [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of anti-HBe seroconversion with entecavir at 4 years and with tenofovir at 5 years are 38% and 40%, respectively [Marcellin et al 2013;Ono et al 2012]. A sustained off-treatment response (persistence of anti-HBe seroconversion) can be expected in 40-80% of these patients [Reijnders et al 2010;Lee et al 2010]. Anti-HBe seroconversion is less durable after therapy is stopped compared with spontaneous anti-HBe seroconversion [Chaung et al 2012] and compared with pegylated interferon therapy [Wong et al 2010].…”
Section: Stopping Nucsmentioning
confidence: 99%
“…After the occurrence of HBeAg seroconversion, additional antiviral therapy is needed for at least one more year to prevent relapse in HBeAg positive chronic hepatitis B [39]. In HBeAg negative chronic hepatitis B patients, it is recommended to treat with an oral antiviral agent until HBsAg loss occurs, because the moment of HBeAg seroconversion does not appear [2].…”
Section: When To Stop?mentioning
confidence: 99%